Evaluation of substituted ebselen derivatives as potential trypanocidal agents. Issue 3 (1st February 2017) - Gordhan, Heeren M.; Patrick, Stephen L.; Swasy, Maria I.; Hackler, Amber L.; Anayee, Mark; Golden, Jennifer E.; Morris, James C.; Whitehead, Daniel C.
Graphical abstract: Abstract: Human African trypanosomiasis is a disease of sub-Saharan Africa, where millions are at risk for the illness. The disease, commonly referred to as African sleeping sickness, is caused by an infection by the eukaryotic pathogen, Trypanosoma brucei . Previously, a target-based high throughput screen revealed ebselen ( EbSe ), and its sulfur analog, EbS, to be potent in vitro inhibitors of the T. brucei hexokinase 1 (TbHK1). These molecules also exhibited potent trypanocidal activity in vivo . In this manuscript, we synthesized a series of sixteen EbSe and EbS derivatives bearing electron-withdrawing carboxylic acid and methyl ester functional groups, and evaluated the influence of these substituents on the biological efficacy of the parent scaffold. With the exception of one methyl ester derivative, these modifications ablated or blunted the potent TbHK1 inhibition of the parent scaffold. Nonetheless, a few of the methyl ester derivatives still exhibited trypanocidal effects with single-digit micromolar or high nanomolar EC50 values.